IBÁÑEZ JIMÉNEZ, J.W. (2013). El contrato de instrumentos derivados (ICADE. Revista de la Facultad de Derecho, 2014)
Autor: Javier Wenceslao Ibañez JiménezEditorial: CivitasAño de publicación: 2013. 360 págs.ISBN: 9788447045297